1993
DOI: 10.1111/j.1365-2125.1993.tb05686.x
|View full text |Cite
|
Sign up to set email alerts
|

The measurement of a new antimicrobial quinolone in hair as an index of drug exposure.

Abstract: 1. Scalp hair samples were obtained at 1 month intervals up to 5 months from healthy male volunteers participating in a phase I study of a new antimicrobial quinolone, OPC‐17116. 2. Hair was sectioned into 1 cm lengths from the scalp end. Corresponding portions from five pieces of hair were dissolved in 1 N NaOH and assayed for OPC‐17116 by h.p.l.c. 3. In all subjects taking a single dose (400 mg, n = 5) or repeated doses (400 mg day‐1, twice daily, for 6.5 days, n = 6), the drug was detected in the portions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Others have reported on a wide variety of substances that can be recovered from human hair samples and can be quantitatively determined. These include nicotine and cotinine [7], caffeine [8], antipsychotics and anti-anxiety medications [9,10,11,12], various antibiotics [13,14,15,16], pesticides [17], digoxin [18], and steroids [19,20]. There are several advantages to hair as a sample for analysis, but the single most important attribute is undoubtedly the long retrospective time frame to which analysis of a segment of hair corresponds.…”
Section: Introductionmentioning
confidence: 99%
“…Others have reported on a wide variety of substances that can be recovered from human hair samples and can be quantitatively determined. These include nicotine and cotinine [7], caffeine [8], antipsychotics and anti-anxiety medications [9,10,11,12], various antibiotics [13,14,15,16], pesticides [17], digoxin [18], and steroids [19,20]. There are several advantages to hair as a sample for analysis, but the single most important attribute is undoubtedly the long retrospective time frame to which analysis of a segment of hair corresponds.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that an ingested drug, whether administered continuously or intermittently, is deposited in hair in proportion to the dose and that it is captured there, moving outwards along the shaft as the hair grows [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Therefore, it may be possible to consider a strand of hair as a "tape-recorder," which continuously stores all the data about the drug exposure of individual over the past several months, or possibly years.…”
Section: Discussionmentioning
confidence: 99%
“…4), depending on the weight of the hair and its melanin content. Therefore, data from pooled segments obtained from different hairs may well produce a broadened distribution, with tailing at the point of any change in drug exposure [16]. In addition, it is easier to sample just a few hair strands, because plucking them does cause some discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…I have found that ofloxacin, an antimicrobial quinolone derivative that is frequently prescribed in Japan, can be detected in hair after even a short exposure (Miyazawa et al 1991Uematsu et al 1991aUematsu et al , 1992.…”
Section: Estimating the Hair Cycle Stage And Growth Ratementioning
confidence: 98%